KONSISTENSI RASM DAN ḌABȚ MUSHAF KUNO NUSANTARA(Analisis Mushaf Kuno Simalungun Sumatera Utara) - Nurhasanah Nasution; Ahmad Fathoni (CV. Adiba Aisha Amira, 2024)
The research type of this thesis is qualitative research with literature and field surveys. The primary data source is the Simalungun Ancient Mushaf of North Sumatra, and the secondary data source is any information related to the Ancient Mushaf, rasm, and ḍabț Al-Qur'an. The data analysis is using descriptive analysis method and single text research method. The conclusion in this study is that the use of rasm in the Simalungun Ancient Mushaf of North Sumatera uses rasm uśmānī and imlā'ī. The writing is sometimes consistent with the rules of rasm uśmānī and so do with rasm imlā'ī. While the use of the ḍabț is sometimes the same as the Indonesian Standard Mushaf and sometimes also like the Medina Mushaf. Consistency in the use of ḍabț is found in harakat ḍammah and tanwīn in iẓhār, idgām, ikhfā', or iqlāb. Sukun sign on the letter līn, iẓhār, iẓhār syafawī, idgām mutamāśilaīn, ikhfā', iqlāb, idgām bigunnah, idgām bilā gunnah, and idgām mutaqāribaīn